The role of physical variables in biodiversity patterns of intertidal macroalgae along European coasts. (15th December 2016) - Puente, Araceli; Guinda, Xabier; Juanes, Jose A.; Ramos, Elvira; Echavarri-Erasun, Beatriz; De La Hoz, Camino F.; Degraer, Steven; Kerckhof, Francis; Bojanić, Natalia; Rousou, Maria; Orav-Kotta, Helen; Kotta, Jonne; et al.
Abstract : In the frame of the COST ACTION 'EMBOS' (Development and implementation of a pan-European Marine Biodiversity Observatory System), coverage of intertidal macroalgae was estimated at a range of marine stations along the European coastline (Subarctic, Baltic, Atlantic, Mediterranean). Based on these data, we tested whether patterns in macroalgal diversity and distribution along European intertidal rocky shores could be explained by a set of meteo-oceanographic variables. The variables considered were salinity, sea surface temperature, photosynthetically active radiation, significant wave height and tidal range and were compiled from three different sources: remote sensing, reanalysis technique and in situ measurement. These variables were parameterized to represent average conditions (mean values), variability (standard deviation) and extreme events (minimum and maximum values). The results obtained in this study contribute to reinforce the EMBOS network approach and highlight the necessity of considering meteo-oceanographic variables in long-term assessments. The broad spatial distribution of pilot sites has allowed identification of latitudinal and longitudinal gradients manifested through species composition, diversity and dominance structure of intertidal macroalgae. These patterns follow a latitudinal gradient mainly explained by sea surface temperature, but also by photosynthetically active radiation, salinity and tidal range. Additionally, a longitudinal gradient was also detected and could be linked to wave height.